Longitudinal follow-up of antibody response to selected antigens of human papillomaviruses and herpesviruses in patients with invasive cervical carcinoma - Hamsíková, E; Ludvíková, V; Tachezy, R; Kovarík, J; Brousková, L; Vonka, V (International journal of cancer, 2000)
A group of 21 cervical-carcinoma patients was followed longitudinally. All patients had undergone intensive radiotherapy. In the course of a more than 5-year observation period, 2 patients died of cervical cancer, 1 from other causes, 3 were lost from follow-up, and 15 survived without any signs of the disease. Sera taken before, up to 17 months after and more than 5 years after the start of therapy, were tested by ELISA for IgG antibodies reactive with a broad spectrum of HPV-derived antigens, glycoprotein G of HSV 2, whole virion antigen of HCMV, and a synthetic peptide corresponding to the immuno-dominant region of EBNA 1. The therapy was associated with a marked decrease in E2 and E7 antibodies in nearly all patients possessing pre-existing antibodies; the changes in VLP antibody levels in the treated women were more rare and less pronounced. In the course of the observation period, seroconversion to gG HSV2 positivity was seen in 5 patients, while, a marked increase in pre-existing gG HSV2 antibodies was observed in 5 out of 7 originally seropositive patients. At enrollment, only 2 patients were free of HCMV antibody and only 1 was free of EBNA1 antibody; no seroconversion relative to either antigen was seen during the observation period.
Keywords: protilátky virové; senioři; Antibodies, Viral; Female; Humans; Antibody Specificity; Papillomaviridae; následné studie; specificita protilátek; lidé; Follow-Up Studies; nádory děložního čípku; Middle Aged; ženské pohlaví; lidé středního věku; Time Factors; antigeny virové; Herpesviridae; Antigens, Viral; dospělí; Adult; časové faktory; Aged; Uterine Cervical Neoplasms